Hiperialitas Konsep Cantik dan Perempuan dalam Film: Analisis Semiotik pada Film Imperfect - Rhesa Zuhriya Briyan Pratiwi; Achmad Abdul Azis (UIN Raden Mas Said Surakarta, 2022)
Imperfect is one of the interesting films because it tells about the reality of women in relation to the stereotype of being beautiful and perfect. The purpose of this research is to examine the description of women's beauty discourse represented through the film Imperfect, including in its substance related to career, love, and the size of beauty that is seen physically (body size and shape) in women. Through the analysis of Sara Mills, this research was analyzed qualitatively descriptively, with the main data collection through the documentation on the film Imperfect. The discussion focuses on the position of the subject-object and the position of the reader in the film, the image of women and the beauty represented in it indirectly shows the existence of hyperiality that is believed to be socially in society. The concept of beauty is described as emerging through the construction of body size, including its influence on the career journey and the romance experienced by the character. In addition, the representations that appear also lead to the struggle of Rara (the main character) who tries to meet the standards and assessments of society so that her existence can be accepted socially.